Bacteriophage Cocktail Can Effectively Control Salmonella Biofilm in Poultry Housing - Korzeniowski, Paweł; Śliwka, Paulina; Kuczkowski, Maciej; Mišić, Dušan; Milcarz, Agata; Kuźmińska-Bajor, Marta (Frontiers in Microbiology, 2022)
Salmonella enterica serovar Enteritidis (S. Enteritidis) is the major contaminant of poultry products, and its ability to form biofilms on produced food and poultry farm processing surfaces contributes to Salmonella transmission to humans. Bacteriophages have come under increasing interest for anti-Salmonella biofilm control. In this study, we used the three previously sequenced and described phages UPWr_S1, UPWr_S3 and UPWr_S4 and a phage cocktail, UPWr_S134, containing these three phages to degrade biofilms formed by two S. Enteritidis strains, 327 lux and ATCC 13076, in vitro. It was found that treatment with bacteriophages significantly reduced biofilm on a 96-well microplate (32-69%) and on a stainless steel surface (52-98%) formed by S. Enteritidis 327 lux. The reduction of biofilm formed by S. Enteritidis ATCC 13076 in the 96-well microplate and on a stainless steel surface for bacteriophage treatment was in the range 73-87% and 60-97%, respectively. Under laboratory conditions, an experimental model utilizing poultry drinkers artificially contaminated with S. Enteritidis 327 lux and treated with UPWr_S134 phage cocktail was applied. In in vitro trials, the phage cocktail significantly decreased the number of Salmonella on the surface of poultry drinkers. Moreover, the phage cocktail completely eradicated Salmonella from the abundant bacterial load on poultry drinkers in an experimentally infected chicken model to an undetectable level. Therefore, the UPWr_S134 phage cocktail is a promising candidate for Salmonella biocontrol at the farm level.